Drug Traceability using Blockchain - Nalayini, C.M.; Sarulatha, S.; Akshaya, R. (Journal of Ubiquitous Computing and Communication Technologies, 2024)
The medicine supply tracking system that has been built uses blockchain-based technology to address the widespread problem of counterfeit pharmaceuticals. The solution utilizes the decentralized structure of blockchain to guarantee confidentiality and transparency in the prescribed medicine distribution chain. The blockchain tracks an individual drug's path from producer to customer, providing auditable and immutable documentation of its legitimacy and provenance. Smart contracts automate procedures and enforce pre-established guidelines. "Examples include confirming the authenticity of medicines and triggering alarms for questionable activity. The technique reduces the possibility of counterfeit medicines entering the market by eliminating the need for trust in middlemen through decentralized consensus procedures. In the end, the blockchain-based medicine traceability system improves patient safety by enabling the quick identification and removal of fake medicines from the market.
Keywords: Blockchain; Counterfeit; Immutable documentation; Decentralized; Traceability system